2011
DOI: 10.1055/s-0031-1281490
|View full text |Cite
|
Sign up to set email alerts
|

Hypospadias Repair: An Overview of the Actual Techniques

Abstract: Hypospadias is one of the most common congenital genital anomalies for which surgery early in life is indicated. The surgical treatment is changing progressively, often by repeating treatment strategies that have been used decades ago. Indeed, historically twostage procedures were replaced by one-stage procedures and nowadays two-stage procedures gain new interest. The same for reconstructions using the urethral plate, which decades ago were based on the Thiersch Duplay principle. In the 1980s, preputial onlay… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
58
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 69 publications
(70 citation statements)
references
References 75 publications
0
58
1
Order By: Relevance
“…The choice of the technique was at the treating physician's discretion, but techniques were systematically performed by our 'in house' standards [6]. When applying the incised plate technique, a slightly modified tubularized incised plate (TIP) urethroplasty was applied, with a running single layered suture material, covered by two barrier layers [6].…”
Section: Standard Techniques and Follow-upmentioning
confidence: 99%
See 1 more Smart Citation
“…The choice of the technique was at the treating physician's discretion, but techniques were systematically performed by our 'in house' standards [6]. When applying the incised plate technique, a slightly modified tubularized incised plate (TIP) urethroplasty was applied, with a running single layered suture material, covered by two barrier layers [6].…”
Section: Standard Techniques and Follow-upmentioning
confidence: 99%
“…No technique has ever emerged as a gold standard as no high-level evidence has ever shown the superiority of one technique over another [6,7]. There seems, however, to be an increasing trend in recent decades to perform incised plate urethroplasty for distal hypospadias and two stage urethroplasty for proximal hypospadias [8], and the European Association of Urology (EAU) guidelines even propose an algorithm for choosing a technique [5], but this is only based on low-level evidence.…”
Section: Introductionmentioning
confidence: 99%
“…Gozar and coworkers (16) reported that success rate in the re--operation of proximal hypospadias cases is 60% while in distal cases it is about 89%. Subramaniam et al (22) reviewed the techniques for distal hypospadias repair and concluded that most surgeons prefer this technique. However, this method, which results in complication in about 33% of cases, has not been yet accepted for the proximal hypospadias.…”
Section: Flap Types and Tip Reoperationmentioning
confidence: 99%
“…1 A large proportion of these cases are distally located. 2 Despite this, there is no consensus on the optimal surgical technique for distal hypospadias. 3,4 There are over 300 surgical techniques described for repairing hypospadias.…”
Section: Introductionmentioning
confidence: 99%
“…3,4 There are over 300 surgical techniques described for repairing hypospadias. 2,5 However, the Snodgrass tubularized incised plate urethroplasty (TIP) is perhaps the most commonly performed contemporary repair. 6 A study done by Springer and colleagues surveyed surgeons who operate on hyposadias and found that in distal hypospadias (subcoronal to midshaft), the TIP repair was preferred by 52.9% to 71.0% of participants.…”
Section: Introductionmentioning
confidence: 99%